1992
DOI: 10.1007/bf02280760
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and blood pressure effects of carvedilol in patients with chronic renal failure

Abstract: Summary.The pharmacokinetic and acute systemic haemodynamic effects of a single oral dose of 50 mg carvedilol has been studied in 24 hypertensive patients with chronic renal failure. The patients were stratified into 3 groups according to the creatinine clearance: 1 51-90 ml-min-~; II 26-50 ml. min-1; III 425 ml-rain-1.The area under plasma level time curve AUC, the elimination half-life tl/2, the maximum plasma concentration Cm~, the time to peak concentration tm~x were not significantly different between gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These data for M2, M4, and M5 are consistent with results previously observed in healthy volunteers and patients with hypertension. 14,21 Preclinical studies in conscious rabbits have demonstrated that these metabolites possess β-adrenoceptor blocking activity. 18 Compared to carvedilol, metabolite M4 is approximately 13 times more potent, and metabolite M2 is about 2.5-fold more potent.…”
Section: Discussionmentioning
confidence: 99%
“…These data for M2, M4, and M5 are consistent with results previously observed in healthy volunteers and patients with hypertension. 14,21 Preclinical studies in conscious rabbits have demonstrated that these metabolites possess β-adrenoceptor blocking activity. 18 Compared to carvedilol, metabolite M4 is approximately 13 times more potent, and metabolite M2 is about 2.5-fold more potent.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of carvedilol are not altered significantly in patients with renal disease (Kramer et al 1992). However, in patients with liver disease there are marked alterations in the pharmacokinetics of the drug (table III).…”
Section: Pharmacokinetics In Special Populationsmentioning
confidence: 96%
“…Patients with liver disease also have high plasma carvedilol concentrations, 24 but the half-life of the drug is unchanged. Patients with renal disease have slightly increased plasma carvedilol concentrations 25 ; the pharmacokinetics of carvedilol are not altered in patients undergoing hemodialysis. 26 Drugs that increase cytochrome P-450 activity, such as rifampin, can accelerate the clearance of carvedilol.…”
Section: Pharmacodynamic and Pharmacokinetic Propertiesmentioning
confidence: 96%